O12 OPEN PREPERITONEAL INGUINAL HERNIA REPAIR, TREPP VERSUS TIPP IN A RANDOMIZED CLINICAL TRIAL. (25th November 2021) - Bökkerink, Willem; Koning, Giel; Vriens, Patrick; Mollen, Roland; Akkersdijk, Willem; van Laarhoven, Kees
Abstract: Aim: The preperitoneal mesh position for inguinal hernia repair showed beneficial results regarding Chronic Postoperative Inguinal Pain (CPIP) with low recurrence rates. Two open preperitoneal techniques, the TransREctus Sheath PrePeritoneal (TREPP) and the TransInguinal PrePeritoneal (TIPP) technique, were compared in a randomized clinical trial with the hypothesis of less patients with CPIP after TREPP due to complete avoidance of nerve contact. Materials and Methods: Adult patients with a primary unilateral inguinal hernia were randomized to either TREPP or TIPP in four hospitals. Prior to the trial's start the study protocol was ethically approved and published. Outcomes included CPIP after 1 year (primary outcome) and recurrence rates, adverse events and Health related Quality of Life (secondary outcomes). Follow-up was performed at 2 weeks, 6 months and 1 year. Results: Baseline characteristics were comparable in both groups. Pain was less often present after TREPP at 2 weeks and 6 months, but the CPIP at rest at 1 year was comparable 1.9% after TREPP vs 1.4% after TIPP, p = 0.535). The overall recurrence rate was higher in the TREPP group, 8.9% vs 4.6%, p = 0.022). Corrected for a learning curve for TREPP, no significant difference could be assessed (TREPP 5.7% and TIPP 4.8%, p = 0.591). Conclusions: both the TREPP and TIPP technique resulted in a low incidence of CPIP after 1 year follow-up. The TREPP method can be considered a solid method for inguinal hernia repair if expertise is present. The learning curve of the TREPP techniques needs further evaluation.